Review of designs of modern graders - Sh. K. Mukushev; V. V. Filippi (Вестник СибАДИ)
The review of designs of modern graders of domestic and foreign production is provided in this article, new material on this subject is generalized. Technical characteristics of graders are given, their distinctive features are described. The special attention is paid to the technical solutions connected with modernization of designs of a dump of the grader. Ways of improvement of designs of working body of the grader are designated, the main tendencies of development of designs of modern graders of domestic and foreign production are revealed.